Pervivència d'una biblioteca litúrgica: fragments de còdex de l'Arxiu parroquial de Verdú a la Biblioteca de Catalunya - Gudayol Torelló, Anna (Miscel·lània litúrgica catalana, 2014)
In 1934, a lot of musical scores and manuscript fragments from the Paroissial Archives of Verdu (Catalonia) entered the Biblioteca de Catalunya through the Head of the Music Department, Higini Anglès. The fragments were separated in different manuscripts, and the original provenance was unintentionnally lost. The recent identification of some of the Verdu fragments enables us to enlarge the Verdu papers. It allows also the reconstruction of a medieval liturgical library, and makes us reflect on the procedures longtime at work in libraries and archives.